PENGARUH SANKSI DISIPLIN TERHADAP APARAT KEPOLISIAN YANG MENYALAHGUNAKAN NARKOTIKA TERHADAP PENINGKATAN ANGKA PENGGUNA NARKOTIKA DI KALANGAN KEPOLISIAN - Yodwi Augadinda Puti Taya; Davit Rahmadan; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Narcotics crime is regulated in Law Number 35 Year 2009 concerning Narcotics. The formation of this law is based on considerations, among others, that narcotics on the one hand is a drug or material that is useful in the field of medicine or health services and the development of science and on the other hand can also cause a very detrimental dependency if misused without strict and careful control and supervision.This type of research can be classified in the type of Normative legal research, which reveals legislation relating to legal theories that are the object of research. The approach taken uses a qualitative analysis approach by looking for data both in books, journals and other scientific works related to this research. The data sources used are primary and secondary legal materials.The conclusions that can be obtained from the results of the study are: First, The Effect of Disciplinary Sanctions on Police Officers Who Abuse Narcotics on Increasing Narcotics User Numbers in the Police Sector does not show a decrease in numbers, the condition of weakening discipline and professionalism of members of the National Police which is now starting to often become a public discussion. He often reported in various mass media about disciplinary actions carried out by members of the National Police. Second, the Ideal Concept of Sanctions against Police Officers Abusing Narcotics Any activity or effort aimed at creating community members including Polri members to obey regulations or laws does not guarantee that the community or Polri members will comply with existing regulations. The ideal concept for police officers who abuse narcotics through Pre-emptive Efforts (Development), Repressive Efforts, Preventive Efforts. Therefore, in order to realize the upholding of Polri's disciplinary law, currently in the development of the culture of the Police the police are required to make a change from militaristic to behavior that reflects the Civil Police, is democratic, upholds the rule of law and upholds human rights..Keywords: Crime, Narcotics, Police, Sanctions, Law Enforcement.